The power of the past history and statecraft - edited by Hal Brands (Washington, D.C Brookings Institution Press, 2016)
Leading scholars and policymakers explore how history influences foreign policy and offer insights on how the study of the past can more usefully serve the present.
Includes index.
Keywords: United States--Foreign relations--Case studies